COMPARISON OF THE HEMODYNAMIC CHANGES AS SEEN IN PATIENTS UNDERGOING CESAREAN SECTION WITH HYPERBARIC BUPIVACAINE VERSUS ISOBARIC BUPIVACAINE. - Hamid Raza; Bashir Ahmed; Kamlaish et al. (Journal of University Medical & Dental College, 2016)
ABSTRACT OBJECTIVE: The purpose of the study is to compare and assess the hemodynamic and associated changes that occur in the patient population operated for a lower segment cesarean section (LSCS), when they are given 0.5% hyperbaric bupivacaine versus 0.5% isobaric bupivacaine. METHOD: The method of study is a prospective double blind randomized trial of 60 patients belonging to the ASA 1 and ASA 2 category, who underwent a lower segment cesarean section, and comparative analysis of the efﬁcacy and associated hemodynamic changes of hyperbaric with isobaric bupivacaine. The patient population was segmented into two groups, group A receiving hyperbaric bupivacaine 0.5% as 2.5ml ( 12.5mg dose ) and the second group designated as, group B receiving isobaric bupivacaine 0.5% as 2.5ml ( 12.5mg dose) intrathecally. The resultant sensory and motor blockade was determined using pin prick and bromage scale respectively. RESULTS: There was a signiﬁcant difference found among the two groups under study, when compared at 3min interval regarding the sensory blockade. The level of T6 block was reached in 37% (n=10) patients belonging to group A and 77% (n= 17) patients in group B. It was observed that there was no signiﬁcant change among the two groups at 5min interval regarding sensory and motor blockade respectively. The immediate sensory blockade with isobaric bupivacaine in group B produced greater decrease in the systolic and mean arterial blood pressure when contrasted with hyperbaric bupivacaine in group A at 5min interval, but after time interval of 45min there was no statistically signiﬁcant change observed. CONCLUSION: According to our study the effects of isobaric bupivacaine were more signiﬁcantly predictable, hence have a higher efﬁcacy, when contrasted against hyperbaric bupivacaine in lower section cesarean section spinal anesthesia. Quick sensory blockade with isobaric bupivacaine was associated with more decrease in blood pressures when contrasted with the hyperbaric bupivacaine, but this result is not statistically signiﬁcant.